Exploring the Availability and Influence of LGBTQ+ Student Services Resources on Student Success at Community Colleges: A mixed Methods Analysis. Issue 11 (2nd November 2018) - Nguyen, David J.; Brazelton, G. Blue; Renn, Kristen A.; Woodford, Michael R.
ABSTRACT: Two-year institutions educate a sizeable proportion of college students; however, many of these institutions lack the variety of student support resources available at four-year institutions. An extensive body of scholarship has documented the positive influence of student services resources for diverse student populations at two-year colleges; yet, few studies have examined resources for students marginalized on the basis of gender identity and/or sexual orientation. Utilizing concurrent, mixed-methods data from the National Study of Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ+) Student Success, guided by Bronfenbrenner's (1993) ecological systems theory, we examine the availability of LGBTQ+-specific resources and how they support student success. Specifically, utilizing data from 936 survey respondents, we compare the availability of LGBTQ+ resource centers, LGBTQ+ counseling services, LGBTQ+ career planning, and LGBTQ+ student organizations (Gay/Straight Alliance and LGBTQ+-student organizations) at two-year institutions to bachelor's, master's, and doctoral degree-granting institutions. We also draw on 12 semi-structured interviews conducted with current or former community college students to explore the significance of the availability of identity-specific resources. The findings suggest that LGBTQ+-specific resources facilitated student-defined notions of academic and social success, yet a scarcity of such resources exists. We conclude with implications for practice and future research.